An Overview of WSN in Structural Health Monitoring in Civil Structures: Exploring the Potential of WSNs for Structural Health Monitoring in Civil Structures (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The potency of structural health monitoring (SHM) using wireless sensor networks (WSNs) to reduce the costs associated with the implementation and maintenance of SHM systems has inspired researchers' interest. SHM systems have been used to monitor critical infrastructure including bridges, highrise buildings, and stadiums, and they have the ability to extend the life of structures while also improving public safety. WSNs for SHM encounter specific network design problems due to their high data collection rate. This paper provides a detailed overview of WSN, SHM using WSNs, difficulties using smart sensors for SHM applications. The challenges, desirable properties, and approaches of SHM systems are also outlined in this paper.